HISTOPATHOLOGY OF LIVER AND KIDNEY OF TELEOST, Clarias batrachus OF ARSENIC CONTAMINATED CHHILPURA POND WATER - PICHHODE, MOHNISH; GAHERWAL, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Arsenic contamination in natural water resources has become a great task throughout the world which poses serious health problems, being the toxic agent in the ecosystem. The fishes are exposed to it through their skin, gills and by the intake of arsenic contaminated food and water. In the present investigation histological examination of liver and kidney of Chhilpura pond water treated fishes (Clarias batrachus) has severe histopathological changes like lobules of hepatocyte cell, lytic hepatocytes, mild infiltration, haemorrhage, disruption of normal architecture and fatty degeneration steatosis. In kidney it causes, inflammation, haemorrhage and shrinkage of glomerulus, congestion of vessels and rapture of Bowman’s capsules, etc. The present investigation suggested that the arsenic contaminated water showing high toxicity level.